(untitled) (SCIENCE TIME JOURNAL, 2026)
The article is about theoretical views related to linguopoetic analysis, the aesthetic function of language, the unity of form and content, and the unity of time and space have been analyzed, including the distinctive features found in Uzbek literature, the early manifestations of realistic forms of expression, their characteristics, causes, and interpretations based on theoretical perspectives.